EFISIENSI PUPUK P DAN HASIL PADI (Oryza sativa L.) PADA SAWAH PASIR PANTAI KULONPROGO YANG DIBERI ZEOLIT - Jauhari Syamsiyah; Mulud Suhardjo; Lilis Andriyani (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2009)
Title : Efficiency of P Fertilizer and Yield of Rice (Oryza sativa L.)  at Sandy Soil Paddy Field Kulonprogo that Added Zeolite. The aim of this research were to study the effect of Zeolite to the efficiency of P fertilizer at Sandy Soil Paddy Field Kulonprogo and to know the rate of P fertilizer that gives the highest yield of rice (Oryza sativa L.) . This research was conducted at Krembangan, Panjatan, Kulonprogo from October 2006 to January 2007. This field experiment was arranged in Split Plot Design. Zeolite as a main plot consists of no Zeolite and 750 kgha-1 Zeolite. P fertilizer as sub plot consist of five levels of P fertilizer, i.e. 0, 20, 40, 60, 80 kg SP 36 ha-1. Each treatment was replicated three times so there are 30 plot treatments. Data were analyzed with F test, Kruskal-Wallis Test, DMRT and Correlation test. There is no interaction effect of P fertilizer and Zeolite to P uptake and Physiological Efficiency. Added 750 kg ha-1 Zeolite can increase P uptake 3.04 g/plant and increase efficiency of P fertilizer up to 62.99% in comparison with control. P Fertilizer has significant effect on total tiller number, weight of rice, weight of 1,000 seeds and percentage of rice empty. Until dosage that used in the experiment, response to P fertilizer is linier. P fertilizer 80 kg ha-1 gives the highest rice yield (6.12 kg/7 m2). Keywords: Efficiency, Zeolite, rice plant